Effect Of Growing Medium Composition And Composting Duration Of Sea Casuarina Leaf Waste On The Growth And Yield Of Red Lettuce (Latuca sativa L. var. Red Rapid) - Tegar D. Saputra; Usman; Jafrizal; Rita Hayati; Habiburahman (Perkumpulan Dosen Muda (PDM) Bengkulu, 2026)
This study aimed to determine the interaction and effects of growing media composition and composting duration of Australian pine (Casuarina equisetifolia L.) leaf waste on the growth and yield of red lettuce (Lactuca sativa L. var. Red Rapid), as well as to evaluate the potential use of Australian pine leaf waste as an alternative compost material. The experiment was arranged in a factorial Randomized Complete Block Design (RCBD) with two factors: growing media composition (K0 = 2:1:0, K1 = 2:1:1, K2 = 2:1:2, and K3 = 2:1:3) and composting duration (L1 = 14 days, L2 = 28 days, and L3 = 42 days). A total of 12 treatment combinations were replicated three times, resulting in 36 experimental units. The results showed that there was no significant interaction between the two factors, and the growing media composition had no significant effect on any of the observed parameters. In contrast, composting duration had significant to highly significant effects on plant height, number of leaves, canopy width, fresh weight, and yield per experimental unit. The 42-day composting treatment produced the highest fresh weight (72.05 g) and yield per experimental unit (215.83 g). In conclusion, composting duration played a more important role than growing media composition. A longer composting period produced more mature compost with greater nutrient availability, thereby enhancing the growth and yield of red lettuce.